A multivariate statistical approach to identify the factors influencing the grayanotoxin content of Italian Rhododendron honey. (June 2022) - Lucatello, Lorena; Piana, Lucia; Fasolato, Luca; Capolongo, Francesca
Abstract: This work represents a step in the identification of hazards associated with the consumption of Italian Rhododendron honey, which could contain grayanotoxins, which can be found in plant belonging to genera of the Ericaceae family. An LC-MS/MS method was developed and validated to quantify Grayanotoxin I (GTX I) in 125 Italian Rhododendron honeys collected from 2017 to 2019. Sensitivity and linearity were demonstrated in the range 10–1000 μg kg −1, and a LOQ value of 10 μg kg −1 was obtained. Absolute recovery ranged from 88.2% to 99.3% and no matrix effect was measured. GTX I was found in the 30.4% of the samples, and the concentrations ranged from 12.3 to 103.5 μg kg −1 . Multivariate statistical approaches were applied to investigate the relationship between the presence/absence of GTX I and different honey features (e.g. environmental factors, quality aspects). The main factors affecting the presence of GTX I resulted the environment, province, altitude and the purity of botanical origin. The mean GTX I level detected in the 'positive' Italian Rhododendron honeys was 119–668 times lower than GTX content found in mad honeys, which caused human intoxication, so the probability of an acute toxic syndrome, in this scenario, is remote. Highlights: Rapid and sensitive LC-MS/MS analytical method to quantify GTX I in honey. Thirty eight (30.4%) Rhododendron honeys analysed, were contaminated with GTX I. Several factors affected the prevalence of GTX I in the samples analysed. The possibility of Italian Rhododendron honey causing acute human intoxication is remote. Geographic area and unifloral index are strictly related to the GTX I content.